2016
DOI: 10.1590/1678-4324-2016150396
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Suitable Reference Genes for Gene Expression Normalization in Jatropha curcas L During Development and Under Stress Conditions Using Real Time Quantitative PCR

Abstract: Jatropha curcas L represent a potential source of raw material for the production of biodiesel. The aim this (NormFinder, BestKeeper). In addition, the transcript levels of Jc-SRG-2 seem to be more correlated with stress responses than changes in transcript levels of Jc-SRG-1, mainly of leaves in exposure to 3-12h on PEG and NaCl stress. Taken together, GAPDH and PP2A2 were regarded as being the best reference to provide guidelines for the selection of potential references genes under these study conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…In addition, the current study showed that Actb, one of the most commonly used reference genes in qPCR-based analyses, was only identified as a stable reference gene in the kidney, echoing a previous report using a mouse model of obesity [30]. Overall, like many previous studies [6,7,22], we suggest using no fewer than two reference genes for normalization, which results in more reliable gene expression analysis data.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In addition, the current study showed that Actb, one of the most commonly used reference genes in qPCR-based analyses, was only identified as a stable reference gene in the kidney, echoing a previous report using a mouse model of obesity [30]. Overall, like many previous studies [6,7,22], we suggest using no fewer than two reference genes for normalization, which results in more reliable gene expression analysis data.…”
Section: Discussionsupporting
confidence: 85%
“…In recent years, several research groups have developed algorithms, including GeNorm [15], BestKeeper [16], NormFinder [17], the ΔCt approach [18], and RefFinder [19], to identify the most stable reference gene(s) in a set of samples. Using these algorithms, the stability of various reference genes under specific experimental conditions has been evaluated in many studies of animals and plants [21][22][23]. Although all five algorithms are suitable, RefFinder and GeNorm are considered the best algorithms for evaluation of the most stable reference gene(s) because RefFinder yields more accurate results and GeNorm determines the optimal number of reference genes needed for normalization of qPCR data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Designing specific primers and adopting appropriate probes are crucial requirements for amplification efficiency, specificity and fluorescence in qPCR assays. The primer should be designed in junction exon-exon of genic sequence to avoid amplification of contaminant genomic DNA, amplifying specifically the target cDNA sequence [6]. The primer efficiency might be analyzed employing serial dilutions or standard curves, defining the ideal primer concentration and/or assessing the reaction efficiency.…”
Section: Primer Design and Probe Considerationsmentioning
confidence: 99%
“…UCP -Ubiquitin conjugation protein; Ciclofilin; ACT11 -actin-11; Tα2 -tubulin alpha-2; EF1-α -elongation factor 1-alpha; PP2A2 -protein phosphatase 2A-2; PUB3 -polyubiquitin-3; GAPDH -glyceraldehyde-3-phosphate dehydrogenase; Tβ2 -tubulin beta-2. Adapted with permission from Rocha et al[6].…”
mentioning
confidence: 99%